Disclosure of strategic management accounting information: evidence from award-winning organizations in Malaysia / Bernadette Josephine James, Corina Joseph and Roshima Said - James, Bernadette Josephine; Joseph, Corina; Said, Roshima (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
There is a lack of studies examining the disclosure of strategic management information as a strategy to respond to the global pandemic. This paper examined the extent of the Strategic Management Accounting Disclosure on the 16 National Annual Corporate Report Awards 2020 winners' annual reports using content analysis. A Modified Strategic Management Accounting Disclosure index consisting of 70 disclosure items was employed to measure the extent of the Malaysian public listed companies' strategic management accounting information disclosure. The findings indicated that, on average, 59 out of the 70 items, or 84% of the information listed on the Modified Strategic Management Accounting Disclosure index, were found on all of the annual reports of the award-winning Malaysian organizations. The findings showed that the highest frequency of information disclosed was the new items related to the crisis response plan. The government or the Securities Commission will better understand the impact of future pandemics or crises similar to or worse than the COVID-19 pandemic. Unveiling specific information that needs to be disclosed may support the construction of adequate internal and external policies, help decision-makers optimize sustainability actions, and encourage better use of resources and know-how.